2019
DOI: 10.7759/cureus.4006
|View full text |Cite
|
Sign up to set email alerts
|

Brain Death and Organ Donation Rates in a City Hospital: A Retrospective Study

Abstract: Introduction Although organ donation rates have been increasing over the years, the lack of organ donation remains the most important problem in transplantation. By changing strategies, the Cekirge City Hospital in Bursa/Osmangazi has achieved a cadaveric donor rate of 24.9 per one million individuals in 2016; this rate is 21.5 in England, 20.9 in Norway, 14.7 in the Netherlands, and 10.6 in Germany. Methods Brain death cases were retrospectively evaluated between January 1, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Gender varies between countries in patients diagnosed with brain death. In our study, 52.3% of patients diagnosed with brain death were female gender; studies conducted in our country reported that the majority of those diagnosed with brain death are male sex 7,8,9,10 . Aghighi et al 11 reported from Iran that the rate of brain death in males was 2.1 times that of females and Han et al 12 in a study conducted in South Korea; women were more diagnosed with brain death (65%).…”
Section: Discussionsupporting
confidence: 44%
“…Gender varies between countries in patients diagnosed with brain death. In our study, 52.3% of patients diagnosed with brain death were female gender; studies conducted in our country reported that the majority of those diagnosed with brain death are male sex 7,8,9,10 . Aghighi et al 11 reported from Iran that the rate of brain death in males was 2.1 times that of females and Han et al 12 in a study conducted in South Korea; women were more diagnosed with brain death (65%).…”
Section: Discussionsupporting
confidence: 44%
“…In our hospital, dedicated intensivists participate and act as intermediaries between these trainees and the professional organ procurement team. In a single-center study, well-trained and educated physicians contributed to the increased acceptance of organ donation by patients’ families [ 18 ]. It is speculated that the explanation and participation of the organ donation procedure by a dedicated intensivist, who is more empathetic than the third expert, will contribute to an increase in the organ donation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since physicians serve as decision-makers and advisors in clinical care, it is vital to understand how physicians’ values are challenged by “brain death.” Accordingly, studies done in both Poland and Germany have linked lower organ procurement rates to physicians’ hesitancy in declaring a patient as brain dead even when clear clinical signs were present. [ 7 8 ] One study done in Saudi Arabia among Arab Muslim physicians found that it was permissible to execute any necessary intervention in the event of cardiac arrest for 5% of the “brain dead” patients. [ 9 ] More significantly, a study in Turkey found that 38.2% of the Muslim physicians felt that patients who were diagnosed as “brain dead” should be kept alive for as long as possible.…”
Section: Introductionmentioning
confidence: 99%